Pertumbuhan dan produksi selada (Lactuca sativa l.) pada pemberian berbagai jenis pupuk organik - Sarah Vanda Asprillia; Adriani Darmawati; Widyati Slamet (Journal of Agro Complex, 2018)
The aimed of the research was to analyze the effect the organic fertilizer to increase growth and production of lettuce (Lactuca sativa L.). The Research was conducted on April - July 2017 at Taburmas Garden, Mpu Tantular street, No. 10-12 Bandungan, Semarang. The research design was Completely Randomized Design with 7 treatmentsand 3 replications so that there were 21 units of experiment. The research used organic fertilizer 100 kg N/ha. The treatment were; T0: no organic fertilizer, T1: cow manure (1.15 kg/plot), T2: goat manure (1.16 kg/plot), T3: litter compost (1.5 kg/plot), T4: fertilizer guano (0.226 kg/plot), T5: chicken manure (1,176 kg/plot), T6: rabbit manure (0.763 kg/plot). Data were subjected to Analysis of variance(ANOVA) and continued byDuncan’s Multiple Range Test (DMRT) at α=5%. The results of this study showed that the use of organic fertilizer increased the growth and production of lettuce. Guano ferlitizer and chicken manure fertilizersresulted the highest growth and production in lettuce plants. Keywords : lettuce, organic fertilizer.